Performance analysis of indicators in teaching hospitals after the Health Transformation Plan: a Case Study in Iran - Bahman Ghasemzadeh; Mohammad Amerzadeh; Saeed Shahsavari; Saeideh Moosavi; Abdollah Keshavarz; Aisa Maleki; Rohollah Kalhor (BMC, 2024)
Abstract Background This study aimed to examine the status of performance indicators in hospitals affiliated with Qazvin University of Medical Sciences (QUMS) before and after the implementation of the Health Transformation Plan (HTP). Methods This longitudinal descriptive-analytical study was conducted utilizing hospital data. The study collected data using a checklist that included both general characteristics of the participating hospitals and performance indicators such as "the number of outpatient visits," "the number of paraclinical patients," "the number of surgeries," and "the number of inpatients" on a monthly basis for 2012-2019. The intervention examined in this study was the implementation of the HTP in May 2014. The data collected was analyzed using interrupted time series and STATA statistical software version 15. Results The study examined seven hospitals affiliated with QUMS, including general, trauma, pediatric, gynecology, and psychiatry hospitals. The findings indicated a significant increase in outpatient visits, paraclinical patients, and inpatients in the first month after the intervention. Specifically, there was an increase of 1739 in the number of outpatient visits, an increase of 513 in the number of paraclinical patients, and an increase of 135 in the number of inpatients (p < 0.001). Conclusion The HTP has improved patients' access to medical services. It achieved this by reducing out-of-pocket payments for healthcare services and implementing programs such as developing clinics, improving the quality of visits, and retaining doctors in deprived areas. The reduction in out-of-pocket payments has been particularly beneficial for individuals who lack financial resources and previously faced barriers to accessing healthcare services.